PERSEPSI MAHASISWA TERHADAP MATA KULIAH KEGAWATDARURATAN DALAM PROSES PEMBELAJARAN DARING DAN TATAP MUKA SELAMA MASA PANDEMI COVID-19 - yul afni (Jurnal Ilmiah Cerebral Medika, 2022)
The Covid-19 Pandemic outbreak requires Universities to change the face-to-face learning process into a Brave learning process, and it is hoped that students and lecturers will be able to adapt quickly to these conditions. The purpose of this study was to determine student perceptions of the implementation of courageous learning during the Covid-19 pandemic at Akper Kesdam I/Bukit Barisan Padang. Data was collected by survey using Google Forms. The population in this study were all students of Kindergarten I, II, III Akper Kesdam I/BB Padang totaling 121 people, the sample was taken by using Total Sampling, namely the entire population was used as the research sample. The research instrument used a questionnaire to collect information on student perceptions and the findings in this study from 121 students. A total of 61% of students chose Zoom compared to Google Classroom, which was 39%, related to aspects of the teaching and learning process. Positive perceptions of students were 57% and negative perceptions were 43%. Aspects of Facilities and Infrastructure, negative student perceptions are 52% and positive are 48. Based on these findings, it is expected that universities will optimize the needs of students in the learning process so that the learning process can be carried out properly and optimally.